Restorative Justice in Islamic Law: Solutions to Improve Social Justice Towards a Golden Indonesia 2045 - B. Mutmainnah Sudarmin, Andi; Monika, Monika; Supardi, Maman; Yusrial, Yusrial (El-Rusyd, 2023)
Restorative Justice present as legal reform in Indonesia. Discourse Restorative justice as a legal practice, it is seen as a concept that is more just, has legal certainty, is beneficial and is based on human rights. However, in its application it still experiences many argumentative obstacles so that its use and concept are not yet mature. To this day there is no standard version regarding the concept of restorative justice itself. If examined more deeply, this concept is more similar to the idea of ​​al-’Adalah al-Islahiyah which has existed since the Qur’an was revealed. The type of research used is library research (library research) by using a normative juridical approach regarding regulations and instruments in implementing the concept restorative justice in Indonesia, case study (case approach) related to effectiveness restorative justice in improving justice as well as comparative studies related to the concept a quo based on the view of Islamic law. The data used comes from literature and studies of related verses and hadiths as well as related laws and other regulations of restorative justice. The results of this analysis show that the concept of restorative justice In Islamic law is known asal-adalah al-islahiyah and char. This concept as a whole prioritizes the resolution of matters by emphasizing on reconciliation, forgiveness, restoration and improving the relationship as it is now. This concept is considered more relevant and guarantees rights and justice for the parties so it is considered necessary to be integrated in the system of restorative justice in Indonesia in an effort to realize a golden Indonesia 2045. The implication of this article is that there are standard rules regarding the mechanism for implementing restorative justice in Indonesia by presenting special institutions to accommodate the implementation of restorative justice.